New and little known for the fauna of Kunashir and Sakhalin Islands Lasiocampidae and Noctuoidea (Lepidoptera) - Rybalkin, S.A.; Yakovlev, R.V.; Benedek, B. (Zenodo, 2018)
Rybalkin, S.A., Yakovlev, R.V., Benedek, B. (2018): New and little known for the fauna of Kunashir and Sakhalin Islands Lasiocampidae and Noctuoidea (Lepidoptera). Far Eastern Entomologist 355: 18-22, DOI:10.25221/fee.355.3, URL: http://dx.doi.org/10.25221/fee.355.3